Metabolism of Inositol Phosphates: I. Phytase Synthesis during Germination in Cotyledons of Mung Beans, Phaseolus aureus - Mandal, N. C. (1970)
The degradation of phytin in germinating mung bean seeds has been found to be associated with the increased activity of phytase in the cotyledon. In the differentiated embryo the increase of this activity is very low all throughout the growth periods studied. Phytase appears in the cotyledon during germination. No activity has been detected in the cotyledons of unsoaked seeds. Cycloheximide (10(−6) M) inhibits the appearance of phytase by 61% during 24 and 48 hours after the start of germination. This phytase increase is dependent on the synthesis of new RNA in the cotyledon. Synthesis of DNA is not detected in the cotyledon during germination.